IDEOLOGICAL DIFFERENCES ON THE ISSUE OF AGRARIAN REFORM IN RUSSIA AT THE TURN OF THE XIX–XX CENTURIES - D. N. Geletii (Модернизация, инновация, развитие, 2016)
The paper presents an analysis of various perspectives on the agricultural, institutional changes in Russia, SJ Witte and VK Plehve. The features of these approaches, the analysis of statistical material, which allowed to demonstrate the urgent need to solve the agrarian question in a reactionconservative policy end of the century XIX century.